Acceptance of massive online open course (MOOCs) module among students: the case of UiTM Pulau Pinang / Farleen Azrina Zamberi - Zamberi, Farleen Azrina (Universiti Teknologi MARA, 2021)
Massive online open course (MOOCs) was initiated in Malaysia in 2015 by the Ministry of Education. MOOCs can be considered as the modern and extension of e-learning that allow massive students to learn in an open online course. The idea of MOOCs in higher education is to ensure the university courses are accessible by the students no matter where they are and at any time. MOOCs enable them to share and collaborate learning experiences. The purpose of this research is to survey which factors give high impact to the acceptance of MOOCs learning modules. This survey was conducted by distributing questionnaires to the students in Universiti Teknologi MARA Pulau Pinang, Permatang Pauh Campus. From the analysis, it can be concluded that social influences were the highest factor in influencing the acceptance compared to other factors which were perceived usefulness and perceived ease of use. It can be denied that the social influences can influence the students to use MOOCs in their learning process.